2011
DOI: 10.1016/j.njas.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Actual and potential development of consumer demand on the organic food market in Europe

Abstract: Development of demand for organic foods on three European markets (Denmark, Italy and UK) was investigated by means of quantitative analysis of household panel data and qualitative analysis of consumer life stories and shopping patterns. Potential development was investigated by means of scenario analysis undertaken by experts. Considerable differences between households underlay patterns of increasing aggregate demand at national levels, and fluctuations over time were identified at the household level. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 8 publications
4
39
0
2
Order By: Relevance
“…Across six European countries, Janssen and Hamm (2012) found considerable differences in consumers' willingnessto-pay for organic food depending on how well known the organic logos were and how strict their standards and control systems were perceived to be. Other sources of consumer trust include a producer, a farmer, a retail chain, and an owner of an organic food shop (Essoussi and Zahaf 2009;Janssen and Hamm 2011;Jensen et al 2011;Naspetti and Zanoli 2009;Padel and Foster 2005). For example, a study found that Italian consumers' trust in and purchase of organic food depended on their perception of the retailer's general social performance (Pivato et al 2008).…”
Section: Consumer Trust and Organic Food Consumptionmentioning
confidence: 99%
“…Across six European countries, Janssen and Hamm (2012) found considerable differences in consumers' willingnessto-pay for organic food depending on how well known the organic logos were and how strict their standards and control systems were perceived to be. Other sources of consumer trust include a producer, a farmer, a retail chain, and an owner of an organic food shop (Essoussi and Zahaf 2009;Janssen and Hamm 2011;Jensen et al 2011;Naspetti and Zanoli 2009;Padel and Foster 2005). For example, a study found that Italian consumers' trust in and purchase of organic food depended on their perception of the retailer's general social performance (Pivato et al 2008).…”
Section: Consumer Trust and Organic Food Consumptionmentioning
confidence: 99%
“…Purchase decisions are also affected from external factors such as certification, labeling, packaging and accessibility which have influence on the awareness of the consumers. (Chen et al, 2014;Janssen and Hamm, 2012;Hjelmar, 2011;Jensen et al, 2011;Alizadeh et al, 2008;Murphy, 2008;Schobesberger et al, 2008;Chang and Zepeda, 2004). Demographic and social variables (such as age, gender, education, having children, the size of where they live and some personal traits) of the customers may define organic customers both in a negative and positive way or it is observed in the research that some of the variables are non-effective (Sangkumchalian and Huang, 2012;Shafie and Rennie, 2012;Hjelmar, 2011;Briz and Ward, 2009;Chen, 2007;Schobesberger et al, 2008;Wadoloswka et al, 2008;Onyango et al, 2007;Lockie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While some of the consumers state that they accept paying higher prices for organic products (because of reasons such as feelings of good conscience, health concerns, having children or babies), the limits of purchasing is ambiguous. In some cases, high prices of organic products may also become a barrier to purchasing organic food (Sangkumchalian and Huang, 2012;Probst et al, 2012;Jensen et al, 2011;Michaelidou and Hassan, 2010;Zander and Hamm, 2010;Wadolowska et al, 2008;Kihlberg and Risvik, 2007;Chang and Zepeda, 2004;Lockie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pivato et al [9] study the impact of corporate social responsibility on consumer trust and the impact of that trust on consumers behaviors. Some papers consider consumer trust in organic consumption without systematically controlling for other important determinants of consumer choices [25][26][27]. Nuttavuthisit and Thøgersen [7] first explicitly investigate the importance of consumer trust for the emergence of a market for organic products, and find that the lack of consumer trust is a barrier for the development of a market for organic food.…”
Section: Related Literaturementioning
confidence: 99%